Research on inhibitory effect of mixed suppressants CaCO3, KCl, and K2CO3 on coal dust explosion pressure - Tianqi Liu; Kenan Liu (Scientific Reports, 2024)
Abstract To discuss the inhibitory effect of micrometer scale coal dust explosion pressure, three types of explosion suppressants are selected for mixed explosion suppression. The results indicate that the coal dust explosion process includes three stages: accelerated and decelerated energy release, as well as energy dissipation. When using explosive suppressants, K2CO3 has the greatest inhibitory effect on coal dust explosion, followed by KCl, and CaCO3 has the smallest effect. The K2O, K2O2, and KOH generated by the thermal decomposition of K2CO3 can also block the heat transfer of coal dust, playing a good role in suppressing explosions. The explosion suppression effect of mixing CaCO3 and K2CO3 is better than that of mixing CaCO3 and KCl, and is worse than the explosion suppression effect of using K2CO3 alone. The synergistic effect of KCl and K2CO3 mixed explosion suppression makes the suppression effect better than using K2CO3 alone. This is because KCl generates K2O during pyrolysis, promoting the dynamic equilibrium of K2CO3 explosion suppression process. This makes mixed explosion suppression more worthy of attention and adoption when considering purchase costs.